A novel copper nanoparticles/bean dregs-based activated carbon composite as pseudocapacitors. (May 2017) - Teng, Yuan; Liu, Kun; Liu, Ruihua; Yang, Zeng; Wang, Luo; Jiang, Haixia; Ding, Rui; Liu, Enhui
Graphical abstract: Highlights: Activated carbon derived bean dregs and the CuNPs/AC are used as pseudocapacitors. The CuNPs can be effectively deposited on the surface of AC for preparing CuNPs/AC. The CuNPs/AC has lower R ct, higher energy and power densities than the AC electrode. Abstract: A novel copper nanoparticles/bean dregs-based activated carbon composite (CuNPs/AC) for pseudocapacitors has been successfully prepared by the electroless plating and thermal treatment method. The physical properties of materials were characterized by XRD, SEM, TEM and nitrogen adsorption/desorption isotherm measurements. Electrochemical performances of electrodes were measured by electrochemical impedance spectroscopy, cyclic voltammetry, galvanostatic charge/discharge and cycle life. Research results show that the CuNPs could be effectively deposited onto the surface of AC for preparing Cu-activated carbon composites. Moreover, the CuNPs/AC electrode exhibits low charge-transfer resistance of 1.68 Ω, high specific capacitance (268 F g −1 at 1 A g −1 ), good rate performance, considerable energy and power densities of 31.8 W h kg −1 and 502.9 W kg −1, good cycling stability with 88.5% capacitance retention after 3000 cycles at 2 A g −1 in 4 M [Cu(NO3 )2 + NH4 NO3 ] (CN + NN) redox active electrolytes, indicating that the CuNPs/AC composite would be a promising electrode materials for pseudocapacitors.